2006
DOI: 10.1063/1.2221679
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear instabilities and pathways of rupture in thin liquid bilayers

Abstract: A long-wave nonlinear analysis of dewetting of thin (<100 nm) liquid bilayers on solid substrates is presented. The short and the long time dynamics, interfacial morphologies, and the pathways of rupture and dewetting are studied to assess the roles of interfacial energies, film thicknesses, and viscosities. The twin interfaces (liquid-liquid and liquid-air) of bilayers under the influence of attractive van der Waals forces show a variety of dewetting pathways which, depending on the interfacial energies and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
110
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(111 citation statements)
references
References 44 publications
1
110
0
Order By: Relevance
“…As compared to single-layer films, the complexity of the free energy and dynamics in bi-layer systems is significantly higher [19][20][21][22] then the single-layer because of the increase in the pairs of interfaces (three in bi-layers vs one in single-layer) and the possibility for deformation to occur via bending and squeezing modes, as shown in Fig. 1(a), which are absent in single-layer films.…”
Section: Introductionmentioning
confidence: 93%
“…As compared to single-layer films, the complexity of the free energy and dynamics in bi-layer systems is significantly higher [19][20][21][22] then the single-layer because of the increase in the pairs of interfaces (three in bi-layers vs one in single-layer) and the possibility for deformation to occur via bending and squeezing modes, as shown in Fig. 1(a), which are absent in single-layer films.…”
Section: Introductionmentioning
confidence: 93%
“…Figure 1 shows the schematic diagram of the bilayers on top of (a) physically heterogeneous and (b) chemically patterned substrate. Detailed theoretical studies into the different features of short and long time instabilities of ultra-thin bilayers have also been recently conducted (Danov et al 1998a, b;Paunov et al 1998;Bandyopadhyay et al 2005Bandyopadhyay and Sharma 2006, 2010Pototsky et al 2004Pototsky et al , 2005Pototsky et al , 2006Nepomnyashchy and Simanovskii 2006a, b, 2007, 2009aMerkt et al 2005;Kumar and Matar 2004;Matar et al 2005;Golovin 2005, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…However, some recent studies [36][37][38][39][40][41][42][43][44] have indicated that kinetic forces also greatly inuence the instability of the thin polymer bilayer, as a result the instability could become a kinetically controlled one. Bandyopadhyay et al 36 have shown that a marked decrease in the viscosity of the upper layer increases the rate of deformation of the upper interface, causing the instability shiing back to the upper interface. Our previous paper 43 has reported that the interfacial slip effect can greatly inuence the instability mode of the thin polymer bilayer.…”
Section: Introductionmentioning
confidence: 99%